2023
DOI: 10.1186/s12885-023-11062-3
|View full text |Cite
|
Sign up to set email alerts
|

Association of pre-treatment lymphocyte-monocyte ratio with survival outcome in patients with head and neck cancer treated with chemoradiation

Abstract: Background Given the role of systematic inflammation in cancer progression, lymphocyte-monocyte ratio (LMR) from peripheral blood has been suggested as a biomarker to assess the extent of inflammation in several solid malignancies. However, the role of LMR as a prognostic factor in head and neck cancer was unclear in several meta-analyses, and there is a paucity of literature including patients in North America. We performed an observational cohort study to evaluate the association of LMR with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 28 publications
(31 reference statements)
1
0
0
Order By: Relevance
“…23 A study of 476 patients by Yu et al demonstrated that a lymphocyte-monocyte ratio < 3.8 (corresponding to MLR > 0.26) was associated with lower overall survival. 24 Our findings supported prognostic value of PLR,NLR, and MLR and quantified thresholds for clinical guidance (FCR=1.25)…”
Section: Survivalsupporting
confidence: 82%
“…23 A study of 476 patients by Yu et al demonstrated that a lymphocyte-monocyte ratio < 3.8 (corresponding to MLR > 0.26) was associated with lower overall survival. 24 Our findings supported prognostic value of PLR,NLR, and MLR and quantified thresholds for clinical guidance (FCR=1.25)…”
Section: Survivalsupporting
confidence: 82%
“…There are several patient-and tumor-related factors that influence clinical outcomes in HNC. Therefore, the identification of prognostic biomarkers that can improve risk stratification and guide treatment decisions has attracted attention [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%